Just world beliefs mediate the well-being effects of spiritual/afterlife beliefs among older Australians - Schuurmans-Stekhoven, James Benjamin (2021)
Perceiving life as fair – i.e., possessing a belief in a just world (BJW) – protects psychological well-being when confronting adversity. Yet, the accumulation of negative experiences over one’s life often dispels BJW. Tangentially-related research shows that religiosity/spirituality is associated with both BJW and well-being – especially among older adults. According to justice motive theory, these findings imply that religiosity/spirituality might sustain older adult BJW and thereby well-being. After surveying older (aged 42–77; mean age = 56.44; SD = 8.97) primarily female (69%) Australian adults (N = 211), a structural equation model linking spirituality with well-being via BJW is estimated. To isolate the incremental spirituality effect, extraneous influences from age, gender, education level, agreeableness and conscientiousness are also modelled. As anticipated BJW declines with respondents’ age, correlates positively with supernatural/spiritual beliefs and mediates the link between spirituality and well-being. Importantly, including rival explanatory variables did not nullify the mediation. Incrementally validating this distal link to the mediator increases confidence that the finding is robust. Large scale longitudinal research exploring inter-temporal variations in religiosity/spirituality, BJW and well-being is now planned to further understand this possible causal mechanism.
Keywords: Well-being; Spiritual Maturity; Religion; Boomers; Aging/ageing